2018
DOI: 10.3390/colloids2030039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Protein Biosurfactants

Abstract: Surfaces and interfaces are ubiquitous in nature and are involved in many biological processes. Due to this, natural organisms have evolved a number of methods to control interfacial and surface properties. Many of these methods involve the use of specialised protein biosurfactants, which due to the competing demands of high surface activity, biocompatibility, and low solution aggregation may take structures that differ from the traditional head–tail structure of small molecule surfactants. As well as their bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…This shows that even relatively simple stabilizers, can produce a wide range of heterogeneous surface phases. Similar simulations for large numbers of native globular protein molecules are not yet available because of computational limitations 32 . Recent simulations on interfaces stabilized by ellipsoidal colloidal particles, interacting through capillary interactions 33 , do however show similar types of heterogeneous structures, varying from randomly aggregated clusters at low surface coverage, to strand-like structures at high surface coverage.
Figure 4Structures formed by block copolymers at the liquid-vapor interface: ( a ) linear strands (effective dimension d e =1), ( b ) in-plane clusters (1≤ d e ≤2), ( c ) 3d clusters (2≤ d e ≤3), and ( d ) 3d films ( d e =3).
…”
Section: Resultsmentioning
confidence: 99%
“…This shows that even relatively simple stabilizers, can produce a wide range of heterogeneous surface phases. Similar simulations for large numbers of native globular protein molecules are not yet available because of computational limitations 32 . Recent simulations on interfaces stabilized by ellipsoidal colloidal particles, interacting through capillary interactions 33 , do however show similar types of heterogeneous structures, varying from randomly aggregated clusters at low surface coverage, to strand-like structures at high surface coverage.
Figure 4Structures formed by block copolymers at the liquid-vapor interface: ( a ) linear strands (effective dimension d e =1), ( b ) in-plane clusters (1≤ d e ≤2), ( c ) 3d clusters (2≤ d e ≤3), and ( d ) 3d films ( d e =3).
…”
Section: Resultsmentioning
confidence: 99%
“…HPs have been considered in previous molecular simulation studies (e.g., see refs and recent review papers and ). Most studies focused on systems involving a few HP molecules near fluid interfaces (air–water, oil–water, and lipid bilayers in contact with water) and their adsorption onto solid surfaces (self-assembled monolayers, silica) using all-atom (AA) and coarse-grained (CG) models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kubiak and Mulheran suggested that ionic strength and structure of the surface could provide a molecular understanding for the discrepancies in experimental studies on the structure of lysozyme at charged silica interfaces . Similarly, simulations have been long used to understand the conformation of AWI-adsorbed proteins such as enzymes, antifreeze proteins, and hydrophobins, and a number of other globular proteins (i.e., β-lactoglobulin or β-casein). However, there have been limited simulation studies that have looked at the assembly of lysozyme at the AWI. Recently, Cieplak et al presented a coarse-grained model for modeling proteins at the AWI by relating amino acid hydropathy to its preferred orientation at the interface .…”
Section: Introductionmentioning
confidence: 99%